Relationship between Thought-action Fusion (TAF), Morality, and Symptoms of Obsessive-Compulsive Disorder (OCD) - Bukhari, Syeda Javaria (The Lighthouse Journal of Social Sciences, 2023)
Obsessive-Compulsive Disorder (OCD) appears in various forms and is often accompanied by Thought-Action Fusion (TAF), which involves considerations of morality or likelihood. Morality TAF refers to the belief that having a morally bad thought is equivalent to actually performing the action. Likelihood TAF, on the other hand, refers to the belief that thinking about a negative event increases the likelihood of it happening in reality. The purpose of this study is to explore the complex relationship between Thought-Action Fusion, specifically TAF Morality or TAF over religious issues, and the resulting feelings of guilt that manifest as OCD symptoms. Understanding these connections could provide insight into the psychological mechanisms underlying the development of OCD symptoms, potentially leading to more targeted interventions and treatment techniques. The sample consisted of 48 participants, ranging in age from 16 to 50 years old. Data was collected from the psychotherapeutic center of the Department of Psychology at the University of Peshawar and Khyber Teaching Hospital Peshawar. The data was analyzed using t-tests and ANOVA. The results revealed a significant positive correlation between TAF morality and guilt feelings in patients with obsessive-compulsive disorder.